2021
DOI: 10.1097/njh.0000000000000805
|View full text |Cite
|
Sign up to set email alerts
|

Self-perceived Burden

Abstract: The purpose of this article is to critically analyze the concept of self-perceived burden. The Rodgers Evolutionary Model is augmented with concept critique, a dialogic process grounded in critical hermeneutics. Self-perceived burden is a relatively mature concept with psychological, relational, and dimensional attributes that are shaped by culture and sociopolitical structures. The antecedents are demographics, circumstances, diagnoses, symptoms, prognosis, comorbidities, and knowledge and beliefs. The conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…If the family has a good functioning ability, it can reduce the patient's sense of interpersonal imbalance and their self-perceived burden level. At the same time, selfperceived burden is a feeling of guilt and shame caused by the troubles and difficulties they have brought to others (Bigger & Vo, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the family has a good functioning ability, it can reduce the patient's sense of interpersonal imbalance and their self-perceived burden level. At the same time, selfperceived burden is a feeling of guilt and shame caused by the troubles and difficulties they have brought to others (Bigger & Vo, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…If the family has a good functioning ability, it can reduce the patient's sense of interpersonal imbalance and their self‐perceived burden level. At the same time, self‐perceived burden is a feeling of guilt and shame caused by the troubles and difficulties they have brought to others (Bigger & Vo, 2022). Studies have shown that guilt and shame will make them more likely to engage in repeated pessimistic thinking about the event (Oflazian & Borders, 2023; Wang et al, 2022), which for patients with NP is the process of regurgitation of pain.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the lack of detailed data prevents our comprehensive understanding of SPB. Professional psychiatric interviews would help to assess concealing antecedents, such as subjective financial toxicity and emotional distress 4 . In addition, some missing clinical information, such as cancer type and length of stay in the unit, prevented further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Self‐perceived burden (SPB) in particular is a common and troubling concern for terminally ill cancer patients 3 . SPB is defined as “ a multidimensional construct arising from the care recipient's feelings of dependence and the resulting frustration and worry, which then may lead to negative feelings of guilt at being responsible for the caregiver's hardship .” 4 Eventually, it can harm relational (e.g., concealing needs, seclusion, and marginalization), existential (e.g., diminished quality of life), and psychological well‐being (e.g., stress, anxiety, depression, and a wish to die).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, being a burden to others is such a common concern for older adults (Miller et al, 2016; Peek et al, 2016) that it has been linked to feelings of guilt (e.g., Bigger & Vo, 2022). Also, previous studies found that feeling of guilt associated with self-perception as a burden, defined as the distress related to “the perception of being responsible for other relatives’ difficulties associated with an anticipated experience of care” (Pedroso-Chaparro et al, 2021; p. 192), were associated with distress in older adults (Pedroso-Chaparro et al, 2021).…”
mentioning
confidence: 99%